Reutilização de seringas descartáveis no domicílio de crianças e adolescentes com diabetes mellitus Reutilizacion de jeringuillas desechables en el domicilio de niños y adolescentes con diabetes mellitus Reuse of discarded syringes in residences of children and teenagers with diabetes mellitus - Ampario del Rocio Vintimilla Castro; Sonia Aurora Alves Grossi (SciELO, 2007)
O fornecimento inadequado ou insuficiente de medicações e materiais para aplicar insulina, leva às famílias a adotarem estratégias variadas, como a prática de reutilização de seringas na tentativa de minimizar os custos com a doença. Objetivos: avaliar a prática de preparo e aplicação de insulina, evidenciar alterações freqüentes nos locais de aplicação de insulina. Este estudo foi comparativo, transversal, com 199 crianças e adolescentes diabéticos do Ambulatório do Instituto da Criança de São Paulo. Dividiu-se em Grupo A que reutiliza seringas descartáveis e Grupo B não as reutiliza. Estratégia comum foi o reencape da agulha sem limpeza prévia, guarda dentro ou fora da geladeira em recipiente fechado. Maior queixa foi a dor. O Hospital e o enfermeiro foram os responsáveis pela orientação dessa prática. El fornecimiento inadecuado o insuficiente de medicaciones y materiales para aplicar insulina lleva a las familias a adoptar varias estrategias como la práctica de reutilización de jeringuillas intentando minimizar los costos con la enfermedad. Objetivos: evaluar la práctica del preparo y de la aplicación de insulina y evidenciar alteraciones frecuentes en esos locales. Este estudio fue comparativo, transversal con 199 niños y adolescentes diabéticos de Consulta Externa del Instituto del Niño del Hospital de las Clínicas de São Paulo. El grupo fue dividido en: Grupo A que reutiliza jeringuillas desechables y Grupo B que no reutiliza. El re encape de la aguja sin limpieza previa, guardan las jeringuillas dentro del refrigerador y fuera del refrigerador, guardan generalmente en recipientes cerrados. Hubo relato de dolor en . El hospital y el enfermero fueron los responsables por la orientación dada . Inadequate or insufficient supply of medication and material to apply insulin leads families to resort to a variety of strategies, such as the practice of reusing dischargeable syringes in order to reduce the expenses with the illness. This is a study aimed at evaluating the practice of insulin application, analyzing the practice of syringe reuse and describing the most frequent changes of application sites. It is a comparative, transversal survey carried out with 199 diabetic children and adolescents. It was developed at the diabetes' Outpatient Unit of the Hospital das Clínicas' Child Institute, of the University of São Paulo's School of Medicine. The studied population was divided in two groups: in Group A were those who reused the syringes, and in Group B those who did not. A common strategy was rewrapping the needle without previously cleaning it and keeping it inside or outside the refrigerator in a closed container. The most common complaint was pain. The hospital and the nurse were responsible for the orientation for that practice.